Cerrado as a model of extreme environment the first Martian era (Research, Society and Development, 2023)
Brazilian savannas (Cerrado biome) is one of the biomes of Brazil that have geological and environmental characteristics which resemble Mars. However, the number of studies in this environment and their microbial diversity for astrobiological purposes are still scarce in the literature. Thus, the objective of this work is to present aspects of the brazilian savanna (Cerrado biome), which have similar characteristics to the environments of the first Mars era. The chosen method to develop this research was a documentary survey of bibliographies on biotechnology and related areas published through books and scientific articles. Previous information or knowledge was collected in order to contribute significantly to Astrobiology. As a result, it was possible to verify that the Cerrado resembles an environment of the first martian era, being found isolated extremophiles, such as those from Thermobrachium kingdoms, from the phylum actinomycete, in addition to the bacteria Flavibacterium sp.. Finally, based on the results, it is possible to say that Cerrado has very similar characteristics to other analogues terrestrial environments widely used for research in Astrobiology, as it has a great potential and is still little explored.